Software versus hardware: How China's institutional setting helps and hinders the clean energy transition - Anders Hove; Michal Meidan; Philip Andrews-Speed (The Oxford Institute for Energy Studies, 2021)
The global low-carbon energy transition will require major changes to institutional practices and energy industry paradigms with implications for society writ large. A country's existing institutional pattern inevitably shapes the transition, and helps or hinders its progress. This is perhaps especially so in state-dominated systems such as China, which have historically considered energy as a strategic field for reasons of both security and economic development. China has already taken steps to embrace clean energy, even as it remains the world's largest consumer of fossil fuels: Indeed, it is the world's leading producer and consumer of renewable energy in absolute terms today, and the country's leaders speak of encouraging a revolution in energy consumption and production, in line with new targets announced in 2020 to achieve carbon neutrality by 2060. But how successful will China be in introducing the sweeping changes required? At the technological level, such changes could include replacing fossil fuels with renewable energy sources, but they also require institutional shifts, which could entail major market reforms and changes to the structure of the Chinese energy sector, dominated now by SOEs and administrative planning. This paper examines how China's institutional setting both contributes to and hinders the energy transition, with a particular emphasis on the energy sector. It also aims to dispel the binary view of China's governance and the energy transition, in which central government commitment is portrayed as the sole determinant of success. Finally, it sets out a preliminary framework for analysing the areas where technological and institutional factors make change more likely to be lasting and transformative, versus areas in which resistance will likely remain strong. Historically, China has been better at building out energy supplies and adding the 'hardware' of energy infrastructure, while having greater difficulty adjusting the 'software' of institutional and societal change or practices related to energy demand and energy efficiency. We would argue that China is likely to continue to expand the hardware, given its strong institutions devoted to investing in supply. But China will struggle with the software as this relies on a demand pull, market incentives, and greater coordination among stakeholders and between sectors. When considering innovation for the energy transition, the paper makes a similar argument: China's technology innovation system has enabled innovation in first generation technologies. But will China's strong incumbent industries impede the transformational change required for the more modular technologies that are less capital intensive and require greater societal involvement and coordination? China has come to dominate global supplies in manufacturing-intensive technologies - solar photovoltaics and batteries - which have also seen the most rapid cost declines due to scale. For design-intensive technology - such as wind, concentrating solar power plants, or advanced coal plants - cost declines have not been as pronounced. For those technologies that are less modular and more design-intensive, state-owned enterprises may play a larger role and the potential for transformative technological change could be slower to emerge.
Keywords: 330; China; Coal; energy security; Energy Transition; Gas; green financing; innovation; Institutions; Market reform; Oil; Prices; Renewables; Technology